2014
DOI: 10.1016/j.econmod.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth driven by a sequence of general purpose technologies

Abstract: We present a Schumpterian model of endogenous growth with General Purpose Technologies (GPTs) that captures two important historical stylized facts: First, from the beginning of mankind until today GPTs are arriving at an increasing frequency and, second, all GPTs heavily depended on previous technologies. In our model, the arrival of GPTs is endogenous and arises stochastically depending on the currently available applied knowledge stock. This way of endogenizing the arrival of new GPTs allows for a model whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…They showed that the time lag between the deployment of research resources and the beginning of the stream of private revenues from their commercial applications heavily influences the private rate of return to research. (Basu et al, 2006;Comin & Gertler, 2006;Kung & Schmid, 2015) and forces affecting long-run economic growth (Bresnahan & Trajtenberg, 1995;Schaefer et al, 2014).…”
Section: Public Procurement For Innovationmentioning
confidence: 99%
“…They showed that the time lag between the deployment of research resources and the beginning of the stream of private revenues from their commercial applications heavily influences the private rate of return to research. (Basu et al, 2006;Comin & Gertler, 2006;Kung & Schmid, 2015) and forces affecting long-run economic growth (Bresnahan & Trajtenberg, 1995;Schaefer et al, 2014).…”
Section: Public Procurement For Innovationmentioning
confidence: 99%
“…As will be shown in Section 3, we build on these two recent articles and explicitly introduce a stock of useful knowledge when developing our model. More precisely, we rely on the innovative theoretical approach of Schaefer et al (2014) that tracks down the history of technical improvements that accumulate in a stock of useful knowledge. The latter stock then shapes the pattern of arrival of General Purpose Technology (GPT), which in turn impact the rate of change of all kinds of technical changes -distinguished between learning-by-doing and profit-motivated R&D as in Strulik et al (2013) andO'Rourke et al (2013).…”
Section: Useful Knowledge Rather Than Human Capital Of General Populationmentioning
confidence: 99%
“…Following Strulik et al (2013), we have considered two kinds of technical changes: non-profit motivated learning-by-doing occurring in the final good sector, and profit-motivated R&D affecting both final and energy-producing sectors. As suggested by Schaefer et al (2014), all these technical advancements should be interrelated by the evolution of a General Purpose Technology (GPT) referred to as G. Lipsey et al (2005, p. 98) define a GPT as a single generic technology, recognizable as such over its whole lifetime, that initially has much scope for improvement and eventually comes to be widely used, to have many uses, and to have many spillover effects. 23…”
Section: Knowledge and Endogenous Technical Changementioning
confidence: 99%
See 2 more Smart Citations